Analysis on Evolution Law of Small Structure Stress Arch and Composite Bearing Arch in Island Gob-Side Entry Driving. (23rd June 2022) - Huang, Shunjie; Wang, Xiangqian; Li, Yingming; Wang, Lei; Liu, Gang; Xiao, Fukun; Bashkov, O. V.
Abstract : At present, the theory of supporting the surrounding rock small structure of gob-side entry driving has been widely used, but there is no specific quantitative analytical formula for the bearing strength and bearing characteristics of the structure. Construct a small structural stress arch mechanical model based on the arch axis equation, and divide the width of coal pillars (fractured zone-plastic softening zone-plastic hardening zone) and small structural stress arch height. According to the relationship between the stress arch height and the size of the roadway, the anchor cable length is determined to be 7.3 m, and the "anchor mesh + ordinary long anchor cable + grouting anchor cable" coordinated support plan is proposed: anchor net support is used for the first support, and long anchor cable and grouting anchor cable are used for the second support. Combined with the supporting parameters, a mechanical model of the surrounding rock composite bearing stress arch is proposed, and the composite bearing stress arch structure is derived using elastoplastic mechanics to obtain the ultimate bearing strength relationship expression. The results show that the ultimate bearing capacity of the haulage gateway of 17236 island working-face in the north of Zhangji coal mine can reach 29.193 MPa after the composite bearing stress arch support. The feasibility of the supporting scheme is verified, and field monitoring showed that the deformation zone of the surrounding rock of the transportation haulage gateway is stable after being supported by the composite bearing stress arch structure, the maximum shrinkage of the top and bottom of the roadway is 287 mm, and the distance between the two sides is 640 mm.